Anti-migration light-conversion adhesive film and preparation method thereof, and photovoltaic module
By using a photovoltaic composite coated with an organic photovoltaic agent in the photovoltaic film and forming a covalent connection through a specific chemical grafting reaction, the problem of the transfer agent migration and light transmittance is solved, and the anti-ultraviolet aging performance of the photovoltaic module is significantly improved.
Patent Information
- Application Number
- CN202411287958.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The prior art has limited effect in preventing the migration of the light-transforming agent and will lead to a decrease in the light-transmitting property of the light-transforming adhesive film.
A special light-transformation composite is employed, which comprises an organic light-transformation agent coated in a polymethyl methacrylate layer and grafted by epoxy ring opening reaction and silanoxy hydrolysis condensation reaction to form a covalent link on the matrix resin.
Without affecting the light transmittance of the adhesive film, the migration of organic light converters is significantly slowed down, the anti-ultraviolet aging performance of photovoltaic modules is improved, and the power attenuation under ultraviolet light is slowed down.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic encapsulation adhesive films, and in particular to an anti-migration light-conversion adhesive film and a preparation method thereof, and a photovoltaic module. Background Art
[0002] Compared with PERC cells, the overall power attenuation of high-efficiency N-type cells (such as HJT cells and TOPCon cells) is slowed down, which can reduce the cost of photovoltaic power generation. However, high-efficiency N-type cells are sensitive to ultraviolet light. In the presence of ultraviolet light, the power attenuation of the cells is accelerated. To solve this problem, one of the commonly used methods is to introduce light-converting materials into the film inside the photovoltaic module through light regulation to prepare a light-converting film, which converts high-energy ultraviolet light that is harmful to the battery into visible light that can be used and has high power generation efficiency. This method can effectively improve the anti-ultraviolet light aging performance of photovoltaic modules while avoiding shielding ultraviolet light and causing a decrease in the photoelectric conversion efficiency of the module.
[0003] However, in the light-converting film, if the light-converting material is directly added to the matrix resin, the light-converting material will easily migrate out of the surface and diffuse into other structures, which seriously affects the stability of the film's anti-ultraviolet light aging performance. Patent CN116769466A discloses a coated light-converting powder and a photovoltaic film using the light-converting powder. By coating an inorganic layer on the outside of an organic light-converting agent, the light-converting agent is protected and the ultraviolet light resistance is improved. This solution has the following problems: the use of inorganic substances will inevitably cause the light transmittance of the light-converting film to decrease, and the effect of avoiding the migration of the light-converting agent is limited. At present, no solution has been found in the prior art that can effectively solve the migration problem of the light-converting agent and avoid adverse effects on the light transmittance of the light-converting film. Summary of the invention
[0004] In order to solve the above technical problem, that is, the prior art has limited effect in preventing the migration of the light conversion agent and will cause the light transmittance of the light conversion film to decrease, the present invention provides an anti-migration light conversion film and its preparation method, and a photovoltaic module. The light conversion film uses a special light conversion composite, which can slow down the migration of the light conversion agent to a large extent without affecting the light transmittance of the film, thereby improving the anti-ultraviolet light aging performance of the photovoltaic module and slowing down its power attenuation under ultraviolet light.
[0005] The specific technical scheme of the present invention is:
[0006] In a first aspect, the present invention provides an anti-migration light-conversion adhesive film, the raw materials of which include a base resin, a light-conversion compound and an initiator; the light-conversion compound includes: an organic light-conversion agent, a polymethyl methacrylate layer coated on the outside of the organic light-conversion agent, an epoxy silane coupling agent grafted on the outside of the polymethyl methacrylate layer through an epoxy ring-opening reaction, and an alkenyl silane coupling agent grafted on the epoxy silane coupling agent through a silaneoxy hydrolysis condensation reaction.
[0007] In the light conversion composite used in the present invention, the polymethyl methacrylate layer coated on the outside of the organic light conversion agent can slow down the migration of the organic light conversion agent in the film, so that it can be relatively stable in the film and play its role in improving the anti-ultraviolet light aging performance of the photovoltaic module, thereby slowing down the power attenuation of the photovoltaic module under ultraviolet light. In addition, polymethyl methacrylate has a high light transmittance, so after it is introduced into the light conversion film, it will not have an adverse effect on the light transmittance of the film.
[0008] On this basis, the present invention introduces siloxy groups (-SiOR) on the polymethyl methacrylate layer by grafting an epoxy silane coupling agent on the outside, and then further realizes the grafting of a double-bond silane coupling agent. In the above manner, a carbon-carbon double bond can be introduced on the surface of the light-conversion composite. In the process of preparing a photovoltaic film from a base resin, a light-conversion composite and an initiator, the light-conversion composite can be covalently grafted onto the base resin through the carbon-carbon double bond under the action of the initiator, thereby avoiding the migration of the organic light-conversion agent to a greater extent, further improving the anti-ultraviolet light aging performance of the photovoltaic module, and slowing down its power attenuation under ultraviolet light. In addition, by introducing a carbon-carbon double bond on the surface of the light-conversion composite in the above manner, after being used in a light-conversion adhesive film, it will not have an excessive impact on the light transmittance of the film.
[0009] Preferably, the polymethyl methacrylate layer is formed by polymerization of methyl methacrylate and ethylene glycol dimethacrylate in a mass ratio of 4-10:0.1-2.
[0010] Preferably, the organic light conversion agent is one or more of triazine, benzotriazole, polyfluorene and anthracene organic light conversion agents.
[0011] Preferably, the epoxy silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; and the alkenyl silane coupling agent is vinyltrimethoxysilane and / or vinyltriethoxysilane.
[0012] Preferably, the initiator comprises an organic peroxide.
[0013] Further, the organic peroxide includes one or more of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, di-tert-amyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butyl peroxy-3,5,5-trimethylhexanoate and 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane.
[0014] Preferably, the base resin comprises ethylene-vinyl acetate copolymer (EVA).
[0015] Preferably, the raw materials of the anti-migration light-conversion adhesive film further include a cross-linking aid, a cross-linking accelerator, a light stabilizer and a coupling agent.
[0016] Furthermore, the auxiliary cross-linking agent includes triallyl isocyanurate and / or triallyl cyanurate.
[0017] Further, the crosslinking accelerator includes one or more of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, ditrimethylolpropane acrylate, 1,6-hexanediol diacrylate, ethoxylated 1,6-hexanediol diacrylate, propoxylated 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, 1,4-butanediol diacrylate, polyethylene glycol diacrylate, 3-methyl-1,5-pentanediol diacrylate, ethylene glycol dimethacrylate, 2-methyl-1,3-propanediol diacrylate and ethoxylated-2-methyl-1,3-propanediol diacrylate.
[0018] Furthermore, the light stabilizer includes one or more of UV-292, UV-622 and UV-770.
[0019] Furthermore, the coupling agent includes one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinyl bond-containing silane oligomers, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-(acryloxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane.
[0020] In a second aspect, the present invention provides a method for preparing the anti-migration light conversion adhesive film, comprising the following steps:
[0021] (1) melt-blending and extruding a first part of a base resin, a first part of an initiator and a light conversion compound to obtain a light conversion compound masterbatch;
[0022] (2) Blending and forming a film of adhesive film raw materials including the second part of base resin, the second part of initiator and the light-converting composite masterbatch to obtain an anti-migration light-converting adhesive film.
[0023] Compared with directly blending the light conversion compound with all other raw materials to form a film, the present invention first prepares a masterbatch with a part of the matrix resin and the initiator, and then blends it with other raw materials to form a film. This can make the olefinic groups on the surface of the light conversion compound react more fully and form more covalent connections with the matrix resin, thereby further slowing down the migration of the organic light conversion agent in the film, thereby improving the anti-ultraviolet light aging performance of the photovoltaic module.
[0024] Preferably, in step (1), the step of preparing the light conversion complex comprises:
[0025] 1) mixing an emulsifier and an aqueous phase solvent to obtain an aqueous phase; mixing an organic light conversion agent, methyl methacrylate, ethylene glycol dimethacrylate, an addition polymerization initiator and an oil phase solvent to obtain an oil phase;
[0026] 2) The water phase and the oil phase are mixed, emulsified to form an oil-in-water emulsion, and then subjected to addition polymerization, and then the product is separated to obtain core-shell structure particles;
[0027] 3) The core-shell structure particles, epoxy silane coupling agent and ring-opening reaction initiator are mixed to carry out a ring-opening reaction. After the product is separated, the product is mixed with an alkenyl silane coupling agent and a solvent to carry out a hydrolysis condensation reaction, and the product is separated to obtain a light conversion composite.
[0028] In step 2), after the oil-in-water emulsion is formed, the organic light conversion agent exists in the oil phase. Under the action of the addition polymerization initiator, methyl methacrylate and ethylene glycol dimethacrylate undergo addition polymerization, and the organic light conversion agent can be embedded inside. The obtained core-shell structure particles are composed of the organic light conversion agent and the polymethyl methacrylate layer coated on the outside. In step 3), the ring-opening reaction initiator can be pyrolyzed to produce free radicals and carbon dioxide. The carbon dioxide promotes the ring opening of the epoxy group in the epoxy silane coupling agent. The free radicals initiate the formation of free radicals on the polymethyl methacrylate, so that the epoxy group after the ring opening forms a bond with the polymethyl methacrylate, thereby grafting silanoxy groups (-SiOR) on the outside of the polymethyl methacrylate layer, and then these silanoxy groups are used to undergo a hydrolysis condensation reaction with the silanoxy groups in the alkenyl silane coupling agent, and alkenyl groups can be further grafted.
[0029] Furthermore, in step 1), the mass ratio of the organic light conversion agent to methyl methacrylate is 1:1-2.5.
[0030] Furthermore, in step 3), the mass ratio of the core-shell structured particles, the epoxy silane coupling agent and the alkenyl silane coupling agent is 1:1~2:0.5~1.5.
[0031] Furthermore, in step 1), the emulsifier includes sodium lauryl sulfate and polyvinyl alcohol.
[0032] Furthermore, in step 1), the addition polymerization initiator includes azobisisobutyronitrile; in step 2), the addition polymerization reaction temperature is 60-95° C., and the reaction time is 4-8 h.
[0033] Furthermore, in step 3), the ring-opening reaction initiator includes tert-amyl peroxy 2-ethylhexyl carbonate, and the ring-opening reaction temperature is 80-90° C. and the time is 5-8 h.
[0034] Furthermore, in step 3), the temperature of the hydrolysis condensation reaction is 90-100° C., and the time is 3-5 h.
[0035] Preferably, in step (1), the mass ratio of the first part of the matrix resin, the first part of the initiator and the light conversion complex is 94.9-99.9:0.01-0.1:0.1-5.
[0036] Preferably, in step (2), the adhesive film raw materials include, by weight: 90 parts of the second part base resin, 0.1-1 parts of the second part initiator, 5-20 parts of light conversion composite masterbatch, 0.1-1 parts of auxiliary cross-linking agent, 0.1-1 parts of cross-linking accelerator, 0.05-0.5 parts of light stabilizer, and 0.05-0.5 parts of coupling agent.
[0037] In a third aspect, the present invention provides a photovoltaic module, comprising the anti-migration light conversion adhesive film.
[0038] Preferably, the photovoltaic module comprises a lower glass sheet, an anti-migration light-conversion adhesive film, a battery sheet, an anti-migration light-conversion adhesive film and an upper glass sheet which are stacked in sequence.
[0039] Compared with the prior art, the present invention has the following advantages:
[0040] (1) The present invention can slow down the migration of the organic light conversion agent without reducing the light transmittance of the light conversion film by coating the organic light conversion agent with a polymethyl methacrylate layer, thereby slowing down the power attenuation rate of the film under ultraviolet light;
[0041] (2) In the light conversion composite used in the present invention, carbon-carbon double bonds are introduced on the surface of the polymethyl methacrylate layer by sequentially grafting epoxy silane coupling agents and alkenyl silane coupling agents. After being mixed with a base resin and an initiator to form a light conversion adhesive film, the migration of the organic light conversion agent in the adhesive film can be further slowed down, and at the same time, the light transmittance of the adhesive film will not be adversely affected;
[0042] (3) In the process of preparing the light-converting adhesive film of the present invention, the migration of the organic light-converting agent in the adhesive film can be further slowed down by first preparing a master batch with a part of the base resin and the initiator, and then blending it with other raw materials to form a film, thereby improving the anti-ultraviolet light aging performance of the photovoltaic module. DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with the embodiments.
[0044] An anti-migration light-converting adhesive film, the raw materials of which include a base resin, a light-converting compound and an initiator; the light-converting compound includes: an organic light-converting agent, a polymethyl methacrylate layer coated on the outside of the organic light-converting agent, an epoxy silane coupling agent grafted on the outside of the polymethyl methacrylate layer through an epoxy ring-opening reaction, and an alkenyl silane coupling agent grafted on the epoxy silane coupling agent through a silaneoxy hydrolysis condensation reaction.
[0045] As a specific implementation, in the light conversion composite: the polymethyl methacrylate layer is polymerized by methyl methacrylate and ethylene glycol dimethacrylate in a mass ratio of 4~10:0.1~2; the organic light conversion agent is one or more of triazine, benzotriazole, polyfluorene and anthracene organic light conversion agents; the epoxy silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; the alkenyl silane coupling agent is vinyltrimethoxysilane and / or vinyltriethoxysilane.
[0046] As a specific implementation, the initiator includes an organic peroxide; and the base resin includes ethylene-vinyl acetate copolymer (EVA).
[0047] As a specific implementation, the raw materials of the anti-migration light-converting adhesive film further include a co-crosslinking agent, a crosslinking accelerator, a light stabilizer and a coupling agent.
[0048] A method for preparing the anti-migration light-converting adhesive film comprises the following steps:
[0049] (1) melt-blending and extruding a first part of a base resin, a first part of an initiator and a light conversion compound to obtain a light conversion compound masterbatch;
[0050] (2) Blending and forming a film of adhesive film raw materials including the second part of base resin, the second part of initiator and the light-converting composite masterbatch to obtain an anti-migration light-converting adhesive film.
[0051] As a specific implementation, in step (1), the step of preparing the light conversion complex comprises:
[0052] 1) mixing an emulsifier and an aqueous phase solvent to obtain an aqueous phase; mixing an organic light conversion agent, methyl methacrylate, ethylene glycol dimethacrylate, an addition polymerization initiator and an oil phase solvent to obtain an oil phase;
[0053] 2) The water phase and the oil phase are mixed, emulsified to form an oil-in-water emulsion, and then subjected to addition polymerization, and then the product is separated to obtain core-shell structure particles;
[0054] 3) The core-shell structure particles, epoxy silane coupling agent and ring-opening reaction initiator are mixed to carry out a ring-opening reaction. After the product is separated, the product is mixed with an alkenyl silane coupling agent and a solvent to carry out a hydrolysis condensation reaction, and the product is separated to obtain a light conversion composite.
[0055] As a specific implementation, in step (1), the mass ratio of the first part of the base resin, the first part of the initiator and the light conversion complex is 94.9~99.9:0.01~0.1:0.1~5.
[0056] As a specific implementation, in step (2), the adhesive film raw materials include, by weight: 90 parts of the second part base resin, 0.1-1 parts of the second part initiator, 5-20 parts of light conversion composite masterbatch, 0.1-1 parts of auxiliary cross-linking agent, 0.1-1 parts of cross-linking accelerator, 0.05-0.5 parts of light stabilizer, and 0.05-0.5 parts of coupling agent.
[0057] In a third aspect, the present invention provides a photovoltaic module, comprising the anti-migration light conversion adhesive film.
[0058] As a specific implementation, the photovoltaic module includes a lower glass sheet, an anti-migration light-conversion adhesive film, a battery sheet, an anti-migration light-conversion adhesive film and an upper glass sheet which are stacked in sequence.
[0059] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.
[0060] Example 1
[0061] The anti-migration light-transfer adhesive film was prepared by the following steps (the amount of each substance is measured by weight):
[0062] (1) Preparation of core-shell structured particles:
[0063] 0.2 parts of sodium dodecyl sulfate and 0.2 parts of polyvinyl alcohol were added to 84.9 parts of deionized water and stirred to dissolve to obtain an aqueous phase. 6 parts of 2,4,6-tris(1-naphthylethyl)-s-triazine (TNNA-1) and 6 parts of methyl methacrylate, 1 part of ethylene glycol dimethacrylate, 0.2 parts of hexadecanol, and 1.5 parts of azobisisobutyronitrile were stirred evenly to obtain an oil phase. The aqueous phase and the oil phase were mixed and homogenized in a homogenizer, and the speed was controlled at 20000 r / min to obtain an oil-in-water emulsion. The oil-in-water emulsion was transferred to a three-necked flask, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and a temperature of 80°C for 6 h. The reaction solution was centrifuged in a centrifuge at 11500 r / min, and the precipitate after centrifugation was repeatedly washed and centrifuged with deionized water and ethanol to obtain core-shell structure particles.
[0064] (2) Preparation of light conversion complex:
[0065] 1 part of the core-shell structure particles was ultrasonically dispersed in 1 part of γ-glycidyloxypropyltrimethoxysilane, and then 0.01 part of tert-amyl peroxide 2-ethylhexyl carbonate was added, stirred at 85°C for 6 hours, and then washed and filtered to form a wet cake. The wet cake was then dispersed in a mixed solvent consisting of 8 parts of methanol and 2 parts of water, and 1 part of vinyltrimethoxysilane was added. The temperature was controlled at 100°C for 4 hours, centrifuged, washed, and freeze-dried to obtain a light conversion complex.
[0066] (3) Preparation of light-converting composite masterbatch:
[0067] 3 parts of light conversion compound, 0.05 parts of tert-butyl peroxide 2-ethylhexyl carbonate and 97 parts of EVA resin were introduced into a twin-screw extruder through a loss-in-weight scale, melt-extruded and pelletized at 150° C. to obtain a light conversion compound masterbatch.
[0068] (4) Preparation of light-converting film:
[0069] The following materials were weighed by weight: 90 parts of EVA resin, 10 parts of light-converting composite masterbatch, 0.7 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane trimethacrylate, 0.4 parts of 3-methacryloxypropyl trimethoxysilane, and 0.1 parts of light stabilizer UV-770. All the above materials were injected into a mixer and mixed at high speed for 6 hours. After the additives were completely absorbed, the film was cast and extruded at 100°C to obtain an anti-migration light-converting film with a gram weight of 400 g / cm 2 .
[0070] The anti-migration light-conversion adhesive film prepared in this embodiment is used to prepare a photovoltaic module, and the steps are as follows: the anti-migration light-conversion adhesive film, HJT battery cell, anti-migration light-conversion adhesive film and upper glass sheet are sequentially stacked on the lower glass sheet, and then placed in a laminator for heating, vacuuming, laminating, maintaining pressure, and then taking out and cooling to obtain a photovoltaic module.
[0071] Example 2
[0072] The anti-migration light-transfer adhesive film was prepared by the following steps (the amount of each substance is measured by weight):
[0073] (1) Preparation of core-shell structured particles:
[0074] Add 0.1 parts of sodium dodecyl sulfate and 0.1 parts of polyvinyl alcohol to 91.1 parts of deionized water and stir to dissolve to obtain an aqueous phase. Stir 4 parts of 2,4,6-tris(1-naphthylethyl)-s-triazine (TNNA-1) and 4 parts of methyl methacrylate, 0.1 parts of ethylene glycol dimethacrylate, 0.1 parts of hexadecanol, and 0.5 parts of azobisisobutyronitrile to obtain an oil phase. Mix the aqueous phase and the oil phase in a homogenizer and control the speed to 20000 r / min to obtain an oil-in-water emulsion. Transfer the oil-in-water emulsion to a three-necked flask, pass nitrogen protection, and react at a speed of 100 r / min and a temperature of 60°C for 8 h. Centrifuge the reaction solution in a centrifuge at 10000 r / min, and wash the precipitate repeatedly with deionized water and ethanol and centrifuge to obtain core-shell structure particles.
[0075] (2) Preparation of light conversion complex:
[0076] 1 part of the core-shell structure particles was ultrasonically dispersed in 1 part of γ-glycidyloxypropyltrimethoxysilane, and then 0.01 part of tert-amyl peroxide 2-ethylhexyl carbonate was added, stirred at 80°C for 8 hours, and then washed and filtered to form a wet cake. The wet cake was then dispersed in a mixed solvent consisting of 8 parts of methanol and 2 parts of water, and 1 part of vinyltrimethoxysilane was added. The temperature was controlled at 90°C for 5 hours, centrifuged, washed, and freeze-dried to obtain a light conversion complex.
[0077] (3) Preparation of light-converting composite masterbatch:
[0078] 0.1 parts of light conversion compound, 0.01 parts of tert-butyl peroxide 2-ethylhexyl carbonate and 99.9 parts of EVA resin were introduced into a twin-screw extruder through a loss-in-weight scale, melt-extruded and pelletized at 150° C. to obtain a light conversion compound masterbatch.
[0079] (4) Preparation of light-converting film:
[0080] The following materials were weighed by weight: 90 parts of EVA resin, 5 parts of light-converting composite masterbatch, 0.7 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane trimethacrylate, 0.4 parts of 3-methacryloxypropyl trimethoxysilane, and 0.1 parts of light stabilizer UV-770. All the above materials were injected into a mixer and mixed at high speed for 6 hours. After the additives were completely absorbed, they were cast and extruded at 100°C to obtain an anti-migration light-converting film with a gram weight of 400 g / cm 2 .
[0081] The anti-migration light-conversion adhesive film prepared in this embodiment is used to prepare a photovoltaic module, and the steps are as follows: the anti-migration light-conversion adhesive film, HJT battery cell, anti-migration light-conversion adhesive film and upper glass sheet are sequentially stacked on the lower glass sheet, and then placed in a laminator for heating, vacuuming, laminating, maintaining pressure, and then taking out and cooling to obtain a photovoltaic module.
[0082] Example 3
[0083] The anti-migration light-transfer adhesive film was prepared by the following steps (the amount of each substance is measured by weight):
[0084] (1) Preparation of core-shell structured particles:
[0085] 0.5 parts of sodium dodecyl sulfate and 0.5 parts of polyvinyl alcohol were added to 73.5 parts of deionized water and stirred to dissolve to obtain an aqueous phase. 10 parts of 2,4,6-tris(1-naphthylethyl)-s-triazine (TNNA-1) and 10 parts of methyl methacrylate, 2 parts of ethylene glycol dimethacrylate, 0.5 parts of hexadecanol, and 3 parts of azobisisobutyronitrile were stirred evenly to obtain an oil phase. The aqueous phase and the oil phase were mixed and homogenized in a homogenizer, and the speed was controlled at 20000 r / min to obtain an oil-in-water emulsion. The oil-in-water emulsion was transferred to a three-necked flask, nitrogen was introduced for protection, and the reaction was carried out at a speed of 200 r / min and a temperature of 95°C for 4 h. The reaction solution was centrifuged in a centrifuge at 13000 r / min, and the precipitate after centrifugation was repeatedly washed and centrifuged with deionized water and ethanol to obtain core-shell structure particles.
[0086] (2) Preparation of light conversion complex:
[0087] 1 part of the core-shell structure particles was ultrasonically dispersed in 1 part of γ-glycidyloxypropyltrimethoxysilane, and then 0.01 part of tert-amyl peroxide 2-ethylhexyl carbonate was added, stirred at 90°C for 5 hours, and then washed and filtered to form a wet cake. The wet cake was then dispersed in a mixed solvent consisting of 8 parts of methanol and 2 parts of water, and 1 part of vinyltrimethoxysilane was added. The temperature was controlled at 100°C for reaction for 3 hours, centrifuged, washed, and freeze-dried to obtain a light conversion complex.
[0088] (3) Preparation of light-converting composite masterbatch:
[0089] 5 parts of light conversion compound, 0.1 parts of tert-butyl peroxide 2-ethylhexyl carbonate and 95 parts of EVA resin were introduced into a twin-screw extruder through a loss-in-weight scale, melt-extruded and pelletized at 150° C. to obtain a light conversion compound masterbatch.
[0090] (4) Preparation of light-converting film:
[0091] The following materials were weighed by weight: 90 parts of EVA resin, 20 parts of light-converting composite masterbatch, 0.7 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane trimethacrylate, 0.4 parts of 3-methacryloxypropyl trimethoxysilane, and 0.1 parts of light stabilizer UV-770. All the above materials were injected into a mixer and mixed at high speed for 6 hours. After the additives were completely absorbed, the film was cast and extruded at 100°C to obtain an anti-migration light-converting film with a gram weight of 400 g / cm 2 .
[0092] The anti-migration light-conversion adhesive film prepared in this embodiment is used to prepare a photovoltaic module, and the steps are as follows: the anti-migration light-conversion adhesive film, HJT battery cell, anti-migration light-conversion adhesive film and upper glass sheet are sequentially stacked on the lower glass sheet, and then placed in a laminator for heating, vacuuming, laminating, maintaining pressure, and then taking out and cooling to obtain a photovoltaic module.
[0093] Example 4
[0094] The difference between this embodiment and embodiment 1 is that the light-converting composite is not made into a masterbatch, but is directly mixed with other materials to form a film; the rest of the raw materials and preparation process are the same as those of embodiment 1. That is, the steps for preparing the anti-migration light-converting adhesive film in this embodiment are as follows (the amount of each substance is measured in parts by weight):
[0095] (1) Preparation of core-shell structured particles:
[0096] 0.2 parts of sodium dodecyl sulfate and 0.2 parts of polyvinyl alcohol were added to 84.9 parts of deionized water and stirred to dissolve to obtain an aqueous phase. 6 parts of triazine organic light conversion agent: 2,4,6-tris(1-naphthylethyl)triazine (TNNA-1) and 6 parts of methyl methacrylate, 1 part of ethylene glycol dimethacrylate, 0.2 parts of hexadecanol, and 1.5 parts of azobisisobutyronitrile were stirred evenly to obtain an oil phase. The aqueous phase and the oil phase were mixed and homogenized in a homogenizer, and the speed was controlled at 20000 r / min to obtain an oil-in-water emulsion. The oil-in-water emulsion was transferred to a three-necked flask, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and a temperature of 80°C for 6 hours. The reaction solution was centrifuged in a centrifuge at 11500 r / min, and the precipitate after centrifugation was repeatedly washed and centrifuged with deionized water and ethanol to obtain core-shell structure particles.
[0097] (2) Preparation of light conversion complex:
[0098] 1 part of the core-shell structure particles was ultrasonically dispersed in 1 part of γ-glycidyloxypropyltrimethoxysilane, and then 0.01 part of tert-amyl peroxide 2-ethylhexyl carbonate was added, stirred at 85°C for 6 hours, and then washed and filtered to form a wet cake. The wet cake was then dispersed in a mixed solvent consisting of 8 parts of methanol and 2 parts of water, and 1 part of vinyltrimethoxysilane was added. The temperature was controlled at 100°C for 4 hours, centrifuged, washed, and freeze-dried to obtain a light conversion complex.
[0099] (3) Preparation of light-converting film:
[0100] The following materials were weighed in parts by weight: 99.7 parts of EVA resin, 0.3 parts of light-converting compound, 0.705 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane trimethacrylate, 0.4 parts of 3-methacryloxypropyl trimethoxysilane, and 0.1 parts of light stabilizer UV-770. All the above materials were injected into a mixer and mixed at high speed for 6 hours. After the additives were completely absorbed, the film was cast and extruded at 100°C to obtain an anti-migration light-converting film with a gram weight of 400 g / cm 2 .
[0101] The anti-migration light-conversion adhesive film prepared in this example is used to prepare a photovoltaic module in the same manner as in Example 1.
[0102] Comparative Example 1
[0103] The difference between this comparative example and Example 1 is that the organic light conversion agent is not coated with a polymethyl methacrylate layer and grafted with a silane coupling agent; the remaining raw materials and preparation process are the same as those of Example 1. That is, the steps for preparing the light conversion adhesive film in this comparative example are as follows (the amount of each substance is measured in parts by weight):
[0104] (1) Preparation of light conversion agent masterbatch:
[0105] 1 part of 2,4,6-tri(1-naphthylethyl)-s-triazine (TNNA-1), 0.05 parts of tert-butyl peroxide 2-ethylhexyl carbonate and 99 parts of EVA resin were introduced into a twin-screw extruder through a loss-in-weight scale, and melt-extruded and pelletized at a temperature of 150°C to obtain a masterbatch of a light-converting agent.
[0106] (2) Preparation of light-converting film:
[0107] The following materials were weighed by weight: 90 parts of EVA resin, 10 parts of light-converting agent masterbatch, 0.7 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane trimethacrylate, 0.4 parts of 3-methacryloxypropyl trimethoxysilane, and 0.1 parts of light stabilizer UV-770. All the above materials were injected into a mixer and mixed at high speed for 6 hours. After the additives were completely absorbed, they were cast and extruded at 100°C to obtain a light-converting film with a gram weight of 400 g / cm 2 .
[0108] The light conversion adhesive film prepared in this comparative example was used to prepare a photovoltaic module in the same manner as in Example 1.
[0109] Comparative Example 2
[0110] The difference between this comparative example and Example 1 is that the organic light conversion agent is not grafted with a silane coupling agent after being coated with the polymethyl methacrylate layer; the remaining raw materials and preparation process are the same as those of Example 1. That is, the steps for preparing the light conversion adhesive film in this comparative example are as follows (the amount of each substance is measured in parts by weight):
[0111] (1) Preparation of core-shell structured particles:
[0112] 0.2 parts of sodium dodecyl sulfate and 0.2 parts of polyvinyl alcohol were added to 84.9 parts of deionized water and stirred to dissolve to obtain an aqueous phase. 6 parts of 2,4,6-tris(1-naphthylethyl)-s-triazine (TNNA-1) and 6 parts of methyl methacrylate, 1 part of ethylene glycol dimethacrylate, 0.2 parts of hexadecanol, and 1.5 parts of azobisisobutyronitrile were stirred evenly to obtain an oil phase. The aqueous phase and the oil phase were mixed and homogenized in a homogenizer, and the speed was controlled at 20000 r / min to obtain an oil-in-water emulsion. The oil-in-water emulsion was transferred to a three-necked flask, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and a temperature of 80°C for 6 h. The reaction solution was centrifuged in a centrifuge at 11500 r / min, and the precipitate after centrifugation was repeatedly washed and centrifuged with deionized water and ethanol to obtain core-shell structure particles.
[0113] (2) Preparation of light conversion masterbatch:
[0114] 1 part of core-shell structure particles, 0.05 parts of tert-butyl peroxide 2-ethylhexyl carbonate and 99 parts of EVA resin were introduced into a twin-screw extruder through a loss-in-weight scale, and melt-extruded and pelletized at a temperature of 150° C. to obtain a light-converting masterbatch.
[0115] (3) Preparation of light-converting film:
[0116] The following materials were weighed by weight: 90 parts of EVA resin, 10 parts of light-converting masterbatch, 0.7 parts of tert-butyl peroxide 2-ethylhexyl carbonate, 0.7 parts of triallyl isocyanurate, 0.3 parts of trimethylolpropane trimethacrylate, 0.4 parts of 3-methacryloxypropyl trimethoxysilane, and 0.1 parts of light stabilizer UV-770. All the above materials were injected into a mixer and mixed at high speed for 6 hours. After the additives were completely absorbed, they were cast and extruded at 100°C to obtain a light-converting film with a gram weight of 400 g / cm 2 .
[0117] The light conversion adhesive film prepared in this comparative example was used to prepare a photovoltaic module in the same manner as in Example 1.
[0118] Test Case
[0119] The light-converting adhesive films prepared in the embodiments and comparative examples were subjected to a light transmittance test, and the photovoltaic modules prepared in the embodiments and comparative examples were subjected to a UV60kWh ultraviolet aging test. The results are shown in Table 1.
[0120] Table 1 Test results of film transmittance and photovoltaic module UV aging resistance
[0121]
[0122] From Table 1 we can see that:
[0123] (1) Compared with Comparative Example 1, the UV60kWh power attenuation of Example 1 is significantly reduced, and the light transmittance of the film is slightly improved. This indicates that by coating the organic light conversion agent with a polymethyl methacrylate layer and sequentially grafting an epoxy silane coupling agent and an alkenyl silane coupling agent on the outside of the polymethyl methacrylate layer, the migration of the organic light conversion agent can be effectively slowed down without causing a decrease in the light transmittance of the light conversion film, thereby improving the anti-ultraviolet light aging performance of the photovoltaic module. In addition, the reason why the light transmittance of the film of Example 1 is slightly improved may be that the polymethyl methacrylate layer and the silane coupling agent improve the dispersibility of the organic light conversion agent in the film, and can prevent the organic light conversion agent from migrating and aggregating on the surface of the film to affect the light transmittance.
[0124] (2) The UV60kWh power attenuation of Comparative Example 2 is less than that of Comparative Example 1, but greater than that of Example 1. This is because: compared with Comparative Example 1, Comparative Example 2 is coated with a polymethyl methacrylate layer outside the organic light conversion agent, which can slow down the migration of the organic light conversion agent in the film; compared with Comparative Example 2, Example 1 is sequentially grafted with an epoxy silane coupling agent and an alkenyl silane coupling agent outside the polymethyl methacrylate layer. In the process of preparing the base resin, the light conversion composite and the initiator into a photovoltaic film, under the action of the initiator, the light conversion composite can be covalently grafted onto the base resin through the carbon-carbon double bond, thereby avoiding the migration of the organic light conversion agent to a greater extent.
[0125] (3) Compared with Example 4, the UV60kWh power attenuation of Example 1 is smaller. This is because: compared with the method of directly blending the light conversion compound with all other raw materials to form a film in Example 4, in Example 1, the light conversion compound is first prepared into a masterbatch with a part of the matrix resin and the initiator, and then blended with other raw materials to form a film, which can make the olefinic groups on the surface of the light conversion compound react more fully and form more covalent connections with the matrix resin, thereby further slowing down the migration of the organic light conversion agent.
[0126] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.
[0127] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. An anti-migration light conversion adhesive film, characterized in that: The raw materials include a base resin, a light conversion compound and an initiator; the light conversion compound includes: an organic light conversion agent, a polymethyl methacrylate layer coated on the outside of the organic light conversion agent, an epoxy silane coupling agent grafted on the outside of the polymethyl methacrylate layer through an epoxy ring-opening reaction, and an alkenyl silane coupling agent grafted on the epoxy silane coupling agent through a silaneoxy hydrolysis condensation reaction.
2. The anti-migration light conversion adhesive film according to claim 1, characterized in that: The polymethyl methacrylate layer is formed by polymerizing methyl methacrylate and ethylene glycol dimethacrylate in a mass ratio of 4-10:0.1-2.
3. The anti-migration light conversion adhesive film according to claim 1, characterized in that: The organic light conversion agent is one or more of triazine, benzotriazole, polyfluorene and anthracene organic light conversion agents.
4. The anti-migration light conversion adhesive film according to claim 1, characterized in that: The initiator includes an organic peroxide.
5. The anti-migration light conversion adhesive film according to claim 1, characterized in that: The raw materials also include a cross-linking aid, a cross-linking accelerator, a light stabilizer and a coupling agent.
6. A method for preparing the anti-migration light conversion adhesive film according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) melt-blending and extruding a first part of a base resin, a first part of an initiator and a light conversion compound to obtain a light conversion compound masterbatch; (2) Blending and forming a film of adhesive film raw materials including the second part of base resin, the second part of initiator and the light-converting composite masterbatch to obtain an anti-migration light-converting adhesive film.
7. The preparation method according to claim 6, characterized in that: In step (1), the steps of preparing the light conversion complex include: 1) mixing an emulsifier and an aqueous phase solvent to obtain an aqueous phase; mixing an organic light conversion agent, methyl methacrylate, ethylene glycol dimethacrylate, an addition polymerization initiator and an oil phase solvent to obtain an oil phase; 2) The water phase and the oil phase are mixed, emulsified to form an oil-in-water emulsion, and then subjected to addition polymerization, and then the product is separated to obtain core-shell structure particles; 3) The core-shell structure particles, epoxy silane coupling agent and ring-opening reaction initiator are mixed to carry out a ring-opening reaction. After the product is separated, the product is mixed with an alkenyl silane coupling agent and a solvent to carry out a hydrolysis condensation reaction, and the product is separated to obtain a light conversion composite.
8. The preparation method according to claim 7, characterized in that: The mass ratio of the organic light conversion agent to methyl methacrylate in step 1) is 1:1-2.
5.
9. The preparation method according to claim 7, characterized in that: In step 3), the mass ratio of the core-shell structured particles, the epoxy silane coupling agent and the alkenyl silane coupling agent is 1:1-2:0.5-1.
5.
10. A photovoltaic module, characterized in that: It comprises the anti-migration light-converting adhesive film according to any one of claims 1 to 5.
Citation Information
Patent Citations
Coated light conversion powder and photovoltaic adhesive film using same
CN116769466A
Sealant primer and preparation method thereof
CN112694854A
Silica filler and preparation method therefor, and epoxy resin composite material
WO2022120900A1
Cited By
High-reliability light conversion adhesive film and preparation method thereof
CN120383892A